Measuring early child development across low and middle-income countries: A systematic review. (December 2021) - Munoz-Chereau, Bernardita; Ang, Lynn; Dockrell, Julie; Outhwaite, Laura; Heffernan, Claire
The Sustainable Development Goals mandate that by 2030, all children should have access to quality early child development opportunities, healthcare and pre-primary education. Yet validated measures of ECD in low and middle income countries (LMICs) are rare. To address this gap, a Systematic Review (SR) of measures available to profile the development of children between the ages of 0–5 years in LMICs was undertaken. Drawing on education, psychology and health databases, we identified reliable, valid or measures adapted for use in LMICs for either assessments of children's development or their learning environments. The inclusion criteria were (1) peer reviewed papers published between January 2009 and May 2019; (2) assessment tools used to measure cognitive/language development or the early years or home environment in at least one LMIC; (3) report of the psychometric properties (validity and reliability) of the tool, and/or description of the cultural adaptability/translation process undertaken before applying it to a LMIC. Two hundred and forty-nine available records published in the last decade in peer-review journals and nine relevant systematic literature reviews were identified. Fifty-seven records were qualitatively synthesised based on their psychometric properties and cultural adaptation. Forty-three tools were reviewed utilising 12 criteria. Five elements of analysis present in Tables 2 and 3 (study, population tested, validity, reliability and cultural adaptability/translation) focused on the tools' psychometric properties and previous application in LMICs. A further seven dimensions outlined in Tables 4 and 5 identified specific characteristics of the tools from target age, administration method, domains, battery, accessibility, language and country/institution. We suggest these 12 key considerations for the selection of measurement tools that are applicable to effectively assess ECD in LMICs.